Improving the resilience of Free-Space Optical links using structured modes of light - Cox, Mitchell Arij (My University, 2020)
The work presented extends and contributes to research in mitigating the effects of turbulence in long-range Free Space Optical (FSO) links using structured modes of light. While there is an extensive body of existing research in the use of Orbital Angular Momentum (OAM) modes for mode division multiplexed communication channels, there has not been an investigation into the use of alternative mode sets and their resilience to atmospheric turbulence. In this thesis several different approaches are investigated, each with a corresponding journal publication. In the research presented it is found that a carefully chosen subset of Hermite-Gauss modes are significantly more resilient to propagation in turbulence than the more commonly used Laguerre-Gauss modes. Knowledge of this independence is exploited in a “modal diversity” proof-of-principle system which is shown to be effective - an intriguing result which exposes several questions about the propagation of higher order modes in turbulence. In this research it is also found that the resilience of vector vortex modes over scalar vortex modes is in fact a misconception and the choice of mode set for FSO should not be based on its vectorial nature. Motivated by the predominant effects of beam wander in the previous investigations, it is shown that turbulence-induced beam wander is neither a memoryless nor a first order memory system as expected when Taylor ’s frozen-turbulence model is invoked. A more accurate modelling approach for the time-varying nature of turbulence induced beam wander is presented which may be used to design optimised mode sets and digital signal processing schemes in future FSO systems
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy